2020
DOI: 10.18805/lr-4187
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Combining Ability for Seed Yield and Its Related Traits in Blackgram [Vigna mungo (L.) Hepper]

Abstract: An experiment was carried out in blackgram using line x tester mating design to estimate the GCA effect of parents and SCA effect of 54 hybrids for yield and its traits using 27 lines and two testers. The relative estimates of variance due to specific combining ability (SCA) were higher than general combining ability (GCA) variances for all twelve traits, indicating predominance of non-additive gene action. Combining ability estimates showed significant genetic variance in lines for all traits whereas testers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…However, nonsignificant values were observed for pods per cluster in testers and also for interaction and single plant yield in testers. Patial et al (2018) and Patial et al (2022) observed significant variation in blackgram crosses for all the traits studied in the present study.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…However, nonsignificant values were observed for pods per cluster in testers and also for interaction and single plant yield in testers. Patial et al (2018) and Patial et al (2022) observed significant variation in blackgram crosses for all the traits studied in the present study.…”
Section: Resultssupporting
confidence: 56%
“…Hence, all these traits could be improved by pedigree breeding and bi-parental mating programmes. The preponderance of non-additive gene action due to a higher contribution of interaction than the tester to the total variance was also reported by Chakraborty et al (2010) and Patial et al (2022) in blackgram.…”
Section: Resultsmentioning
confidence: 56%
“…The opposing effects of (h) and (l) in crosses II and IV suggests duplicate gene action. Ranjana Patial et al (2022) also reported comparable patterns in the number of branches per plant in black gram. Based on the present results, it is suggested that early selection in segregating generations is not recommended.…”
Section: Scaling Testmentioning
confidence: 69%
“…The preponderance of the partial dominance is in consistent with the studies of Singh et al (2006) for seed yield and protein content in pea and Singh et al (2011) for majority of the traits and over-dominance for number of pods per plant and seed yield per plant in pea. Similarly, Patial et al (2020) revealed over-dominance for days to 50% flowering, days to 75% maturity, plant height (cm), number of branches per plant, number of pods per plant, pod length (cm), number of seeds per pod, 100 seed weight (g), biological yield per plant (g), seed yield per plant (g), harvest index (%) and crude protein content (%). All traits showed non-significant correlation (r) indicating that these traits did not supply any evidence for directional dominance in urdbean for these traits and alleles having increasing and decreasing effects appear to be dominant and recessive to the same extent.…”
Section: Additive and Dominance Componentsmentioning
confidence: 99%